Hyperactive Distal Colonic Motility and Recovery Patterns Following Right Colectomy: A High-Resolution Manometry Study. Issue 4 (18th April 2022) - Wells, Cameron I.; Penfold, James A.; Paskaranandavadivel, Nira; Rowbotham, David; Du, Peng; Seo, Sean; Gharibans, Armen; Bissett, Ian P.; O'Grady, Greg
Abstract : BACKGROUND: Postoperative ileus results in morbidity, prolonged hospitalization, and increased health care expenditure. However, the underlying abnormalities in motility remain poorly understood. Recent high-resolution manometry studies demonstrated that the distal colon becomes hyperactive with a cyclic motor pattern postoperatively, but they did not track this activity beyond 16 hours after surgery. OBJECTIVE: This study used high-resolution manometry to evaluate distal colonic motility during the first 4 days after right-sided colectomy. DESIGN: An observational study of perioperative high-resolution colonic manometry using a 36-sensor catheter with 1-cm resolution. SETTING: A single tertiary hospital. PATIENTS: Adult patients undergoing elective laparoscopic or open right-sided colonic resection. MAIN OUTCOME MEASURES: Occurrence of distal colonic motor patterns during the perioperative period, defined according to a published classification system. Clinical markers of gut recovery included time to first stool, oral diet, and prolonged postoperative ileus. RESULTS: Seven patients underwent perioperative manometry recordings. Hyperactive cyclic motor patterns emerged intraoperatively and peaked in the first 12 hours postoperatively, occupying 81.8% ± 3.9% of the recording. This gradually returned to normal during the first 4 days, reaching 19.0% ± 4.4% ( p = 0.002). No patient had a bowel movement before this hyperactivity resolved. High-amplitude propagating sequences were absent in early postoperative recordings, and their return temporally correlated with the passage of stool. Abnormal high-amplitude repetitive 0.5 to 1 cycle per minute activity was observed in the left colon of 1 patient with prolonged ileus. LIMITATIONS: The invasive nature of recordings limited this study to a small sample size. CONCLUSIONS: Cyclic motor patterns are markedly hyperactive in the distal colon after right-sided colectomy and resolve during the first 4 postoperative days. High-amplitude propagating sequences are inhibited by surgery and gradually recover. Bowel function may not return until these changes resolve. Other abnormal repetitive hyperactive patterns could contribute to the development of prolonged ileus. See Video Abstract at http://links.lww.com/DCR/B967 . MOTILIDAD HIPERACTIVA DEL COLON DISTAL Y PATRONES DE RECUPERACIÓN DESPUÉS DE COLECTOMÍA DERECHA: UN ESTUDIO DE MANOMETRÍA DE ALTA RESOLUCIÓN: ANTECEDENTES: El íleo post-operatorio produce una morbilidad significativa, una hospitalización prolongada y un aumento del gasto sanitario. Sin embargo, las anomalías subyacentes en la motilidad siguen siendo poco conocidas. Estudios recientes de manometría de alta resolución demostraron que el colon distal se vuelve hiperactivo con un patrón motor cíclico en el post-operatorio, pero no registraron esta actividad más allá de las 16 horas posteriores a la cirugía. OBJETIVO: Utilizar la manometría de alta resolución para evaluar la motilidad del colon distal durante los primeros cuatro días después de la colectomía del lado derecho. DISEÑO: Estudio observacional de pacientes sometidos a manometría colónica perioperatoria de alta resolución mediante catéter de 36 sensores con 1 cm de resolución. AJUSTE: Un solo hospital terciario. PACIENTES: Pacientes adultos sometidos a resección laparoscópica o abierta de colon del lado derecho de forma electiva. PRINCIPALES MEDIDAS DE RESULTADO: AAparición de patrones motores del colon distal durante el período perioperatorio, definidos según un sistema de clasificación publicado. Los marcadores clínicos de recuperación intestinal incluyeron, tiempo hasta la primera evacuación, dieta oral e íleo posoperatorio prolongado. RESULTADOS: Siete pacientes fueron sometidos a registros de manometría perioperatoria. Los patrones motores cíclicos hiperactivos emergieron intraoperatoriamente y alcanzaron su punto máximo en las primeras 12 horas post-operatorias, ocupando 81, 8 ± 3, 9% del registro. Esto volvió gradualmente a la normalidad durante los primeros cuatro días, alcanzando el 19, 0 ± 4, 4% (p = 0, 002). Ningún paciente tuvo una evacuación intestinal antes de que se resolviera esta hiperactividad. Las secuencias de propagación de alta amplitud estaban ausentes en las grabaciones post-operatorias tempranas y su retorno se correlacionó temporalmente con el paso de las heces. Se observó actividad anormal de alta amplitud repetitiva de 0, 5-1 ciclo / minuto en el colon izquierdo de un paciente con íleo prolongado. LIMITACIONES: La naturaleza invasiva de las grabaciones limitó este estudio a un tamaño de muestra pequeño. CONCLUSIONES: Los patrones motores cíclicos son marcadamente hiperactivos en el colon distal después de la colectomía del lado derecho y se resuelven gradualmente durante los primeros cuatro días posoperatorios. Las secuencias de propagación de gran amplitud se inhiben mediante cirugía y se recuperan gradualmente. Es posible que la función intestinal no regrese hasta que estos cambios se resuelvan. Otros patrones hiperactivos repetitivos anormales podrían contribuir al desarrollo de íleo prolongado. Consulte Video Resumen en http://links.lww.com/DCR/B967 . (Traducción—Dr. Mauricio Santamaria )